MANAJEMEN KESIAPAN GURU DALAM MENINGKATKAN AKTIVITAS BELAJAR DARING SISWA DENGAN MENGGUNAK MODEL PEMBELAJARAN DI MASA PANDEMIK COVID-19 - Hidayati Hidayati; Muhammad Giatman; Ernawati Ernawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study aims to manage online learning in increasing activities student learning during the covid-19 pandemic for the future, especially in the long term like what we are facing right now with Corona Virus Disease-19 (COVID-19) which doesn't exist yet stop. Through analyzing online learning activity questionnaires through the opinion of an educator or the teacher's point of view with the research sample being 45 teachers who teach at the State Vocational High School in the city of Padang. The instrument used is a questionnaire distributed online using the ms.form link. Based on the data obtained,shows that the implementation of online learning has been carried out effectively seen from the teacher learning model readiness activity. From the results obtained, the teacher's readiness in addressing online learning using a learning model, namely 50% of teachers stated very ready, 20% said they agreed, 10% said they were not ready, 15% said they were not ready and 5% stated when they were not ready to process online learning models, with good results found from the management of educator readiness in online learning in the future can anticipated to be more effective by looking at the deficiencies and obstacles found in the field through this research.